1989
DOI: 10.1002/j.1460-2075.1989.tb03404.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 latency-associated transcripts are evidently not essential for latent infection.

Abstract: The herpes simplex virus type 1 (HSV‐1) transcripts that can be detected during latent infection by Northern blot analysis in human and experimental animal sensory ganglia are encoded by diploid genes. To investigate their role in latent infection we studied HSV‐1 variant 1704, which has deleted most of the IRL copy of the coding region of these RNAs and has a 1.2‐kb deletion that is immediately upstream of the coding region of the TRL copy. During primary infection, 1704 replicated in trigeminal ganglia with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
1
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 20 publications
10
180
1
1
Order By: Relevance
“…1) identified by McGeoch et al (1991) from comparison of the sequences of HSV-1 and HSV-2. Data presented here ( Table 1) which demonstrate that the main determinants of in vitro promoter activity map to a 277 bp region between -279 and -2 (the LAT6 clone) agree with those of a number of other groups (Javier et al, 1988;Dobson et al, 1989;Steiner et al, 1989;Batchelor & O'Hare, 1990;Zwaagstra et al, 1989Zwaagstra et al, , 1990Zwaagstra et al, , 1991Devi-Rao et al, 1991). Zwaagstra et al (1989) initially identified the LAT promoter using a construct similar to pLAT6CAT in Vero cells, and Batchelor & O'Hare (1990) mapped the main determinants of LAT promoter activity in HeLa cells to the 140bp region between -138 and +2.…”
Section: Discussionsupporting
confidence: 83%
“…1) identified by McGeoch et al (1991) from comparison of the sequences of HSV-1 and HSV-2. Data presented here ( Table 1) which demonstrate that the main determinants of in vitro promoter activity map to a 277 bp region between -279 and -2 (the LAT6 clone) agree with those of a number of other groups (Javier et al, 1988;Dobson et al, 1989;Steiner et al, 1989;Batchelor & O'Hare, 1990;Zwaagstra et al, 1989Zwaagstra et al, , 1990Zwaagstra et al, , 1991Devi-Rao et al, 1991). Zwaagstra et al (1989) initially identified the LAT promoter using a construct similar to pLAT6CAT in Vero cells, and Batchelor & O'Hare (1990) mapped the main determinants of LAT promoter activity in HeLa cells to the 140bp region between -138 and +2.…”
Section: Discussionsupporting
confidence: 83%
“…with 25, 50 or 100 ~tl of hyperimmune serum. Infection consisted of inoculation of 106 p.f.u, of HSV-1 strain F or KOS grown to stocks and titrated on CV-1 cells as described previously (Steiner et al, 1989b). Control animals were infected with the same virus strains without prior immunization.…”
Section: Characterization Of An In Vivo Reactivation Model Of Herpes mentioning
confidence: 99%
“…Control animals were infected with the same virus strains without prior immunization. and TG removed for viral titration (Steiner et al, 1989b). Whereas viral replication was detected in the trigeminal ganglia (TG) of non-immunized control mice, no replication was detected in the TG of the mice immunized even with the lowest (25 lal) amounts of hyperimmune serum within 10 days p.i.…”
Section: Characterization Of An In Vivo Reactivation Model Of Herpes mentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream of the IE110 gene is a region of some 3500 bp which has not been assigned any protein coding function but which is the major locus of transcription in neurons latently infected with HSV-1, giving rise to RNA species termed latency-associated transcripts (LATs) (Stevens et al, 1987;Rock et al, 1987;Spivack & Fraser, 1987;Wagner et al, 1988a, b). The function of these RNAs remains obscure, although it has been observed that some HSV-1 variants defective in LAT expression show impaired reactivation from latency in animal models (Leib et al, 1989;Steiner et al, 1989). On the other side of the IE110 gene is a region in which and Ackermann et al (1986) have mapped sequences encoding a protein termed ICP34.5 in HSV-1 strain F, and identified a candidate open reading frame (ORF) for ICP34.5.…”
Section: Introductionmentioning
confidence: 99%